EVALUATING SPLIT TIMING FERTILIZER APPLICATIONS FOR IMPROVING BREAD BAKING QUALITY OF SOFT RED WINTER WHEAT IN KENTUCKY - Williams , Mark A.; Jacobsen , Krista; Phillips, Timothy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
There is growing interest among farmers to locally produce high protein and strong gluten wheat that is suitable for bread making and meet the demand of local artisanal bakers in Kentucky. The warm and humid weather in southeast region is ideal for soft red winter wheat (SRW) production which characterized by low protein content. The technique of splitting nitrogen (N) fertilization according to the growth stages has been suggested to improve protein content and its composition. This study evaluated the effect of split N application on yield and baking quality traits of two SRW wheat cultivars grown in the eastern U.S. region in conventional and organic cropping systems. One landrace (Purple Straw) and one modern cultivar (Pembroke 2014 ) were grown under three split N application treatments (ST1, ST2 and ST3). Late N applications (ST3) significantly increased protein content for both years by 5.45% and 6.11% respectively compared to a single application; however, this treatment decreased yield. Cropping system had consistent effects in that conventional system exceeded organic system except for thousand kernel weight. Conventional system had greater yield by 16.11% and 20.17% respectively for both years than organic system. Similarly, sedimentation value (a baking quality trait) was greater by 14.27% and 11.12% respectively in conventional than organic system. This study has generally found improvement in protein content by N application on soft red winter wheat. In addition, more studies should be done in organic system to examine other baking quality traits.